1995
DOI: 10.1128/jvi.69.2.916-922.1995
|View full text |Cite
|
Sign up to set email alerts
|

Role of cucumovirus capsid protein in long-distance movement within the infected plant

Abstract: Direct evidence is presented for a host-specific role of the cucumovirus capsid protein in long-distance movement within infected plants. Cucumber (Cucumis sativus L.) is a systemic host for cucumber mosaic cucumovirus (CMV). Tomato aspermy cucumovirus, strain 1 (1-TAV), multiplied to the levels of CMV (i.e., replicated, moved from cell to cell, and formed infectious particles) in the inoculated leaves of cucumbers but was completely unable to spread systemically. The defective long-distance systemic movement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(26 citation statements)
references
References 54 publications
1
24
0
Order By: Relevance
“…It has been shown that the 3a protein potentiates cell-to-cell trafficking of CMV RNA in tobacco plants (Ding,B. et al, 1995) and that the CMV CP is able to complement the defective long distant movement of tomato aspermy cucumovirus (TAV) in cucumber plants (Taliansky and Garcia-Arenal, 1995). We have previously identified a novel gene (2b) encoded by the cucumovirus group but which is absent in closely related viruses, such as the bromoviruses and alfalfa mosaic virus (Ding,S.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the 3a protein potentiates cell-to-cell trafficking of CMV RNA in tobacco plants (Ding,B. et al, 1995) and that the CMV CP is able to complement the defective long distant movement of tomato aspermy cucumovirus (TAV) in cucumber plants (Taliansky and Garcia-Arenal, 1995). We have previously identified a novel gene (2b) encoded by the cucumovirus group but which is absent in closely related viruses, such as the bromoviruses and alfalfa mosaic virus (Ding,S.…”
Section: Introductionmentioning
confidence: 99%
“…MPs have been identified in many plant viruses, but the biochemical and molecular mechanisms involved unfortunately are largely unknown. MPs are frequently capsid proteins, as has been demonstrated in tobacco mosaic virus (Dawson et al, 1988;Saito et al, 1990), red clover necrotic mosaic dianthovirus (Xiong et al, 1993;Vaewhongs and Lommel, 1995), cucumber mosaic virus (CMV) (Taliansky and Garcia-Arenal, 1995), and tobacco etch potyvirus (Dolja et al, 1994(Dolja et al, , 1995, among others. Replication proteins such as those involved in genome duplication have also been identified as necessary for long-distance movement in brome mosaic virus (Traynor et al, 1991) and CMV (Gal-On et al, 1994).…”
Section: The Spatiotemporal Transmission Windowmentioning
confidence: 97%
“…Cucumovirus (Cooper et al, 1996;Kaplan et al, 1995) Bromovirus (Nagano et al, 2001) Tobamovirus (Tamai et al, 2003) Potexvirus (Tamai et al,2003) Cucumovirus (Teycheney et al, 2000) Cucumovirus (Salanki et al, 1997;Taliansky and Garcia-Arenal, 1995) Potexvirus (Brigneti et al, 1998) Tobravirus (Liu et al, 2002) Potyvirus (Ryang et al, 2004) Closterovirus (Chiba et al, 2006) Begomovirus (Wege and Siegmund, 2007) Comovirus (Malyshenko et al, 1989) Potyvirus (Guerini and Murphy, 1999;Murphy and Kyle, 1995) Potexvirus (Close, 1964) Cucumovirus…”
Section: Cucumovirusmentioning
confidence: 99%